1997
DOI: 10.1159/000262367
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Caries and Level of Metabolic Balance in Children and Adolescents with Insulin-Dependent Diabetes mellitus

Abstract: The relationship between the occurrence of caries and diabetes was explored in 80 children and adolescents with insulin-dependent diabetes mellitus. The mean age of the subjects was 14.5 years (range 11.7–18.4 years) and duration of diabetes 0.3–15.0 years (mean 6.0 years). DFS indices in poorly controlled subjects (gly-cosylated haemoglobin, HbA1, values over 13%) were significantly higher than in moderately (HbA1 10.0–12.9%) or in well-controlled cases (HbA1 values < 10%). Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
4
8

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 16 publications
9
53
4
8
Order By: Relevance
“…Similar results have been found 11,12,19 in investigations of the prevalence of intact dentitions in relation to the DM status. The present observations support the suggestion that intact dentitions are less frequent only at an earlier stage of their lives among DM adolescents than among metabolically healthy subjects.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results have been found 11,12,19 in investigations of the prevalence of intact dentitions in relation to the DM status. The present observations support the suggestion that intact dentitions are less frequent only at an earlier stage of their lives among DM adolescents than among metabolically healthy subjects.…”
Section: Discussionsupporting
confidence: 85%
“…Karjalainen et al (3) reported that in poorly controlled children and adolescents the DFS (decayed, filled surfaces) indices were significantly high and diabetes was associated with caries. However, the difference was not statistically significant if adjustments were made for age, age at the onset of diabetes and duration of disease.…”
Section: Introductionmentioning
confidence: 99%
“…32 Tükürük akış hızı ve tamponlama kapasitesi azalmış diyabetik bireylerde çürük aktivitesinin de artabileceği gösterilmiştir. 9,33 Bazı çalışmalarda ise Tip 1 diyabet hastalarında tü-kürük akış hızındaki azalmaya rağmen çürük prevalansının değişim göstermediği rapor edilmiştir. 34,35 Daha önce ölümcül seyreden pek çok hastalık, bugün tıp alanındaki gelişmeler sayesinde tedavi edilebilmekte ve buna bağlı olarak yaşam kalitesi yük-selmektedir.…”
Section: Discussionunclassified